Technology, Emotion and Democracy: Understanding The Dynamic Through Analyzing Conversation in Twitter - ADINUGROHO, INDRO; SJAHPUTRI, SMITA; BUDIARTO, JUDOTENS; MUHAMAD, ROBY (Universitas Muhammadiyah Yogyakarta, 2017)
Innovation in technology brings tremendous impact in various areas, including the issues of democracy, politics and government. In this study, authors observe twitter as a digital medium to gather people from diverse background to com- municate each other. Conversation in twitter, known as tweet, could be a gate to represent various political issues. This study aims to analyze valence and arousal of Indonesia’s top political topics in twitter started from November 2015 until May 2016. Top political topics are collected with one primary keyword, jokowi. Each topic is represented with various tweets from different users. The data is collected by specialized computer software namely tracker developed by Provetic Lab. As an attempt to analyze tweets, authors used Algoritma Kata (AK) as the primary instrument to analyze valence and arousal contained in each topic. Re- sult shows when users talked about jokowi and kebanggaan (pride), the conver- sation contained positive valence and high excitement in arousal level. Whereas, when users discussed corruption and other scandal involving Government, the conversation turned into negative valence with different arousal level.